2017
DOI: 10.1037/cdp0000108
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood context, psychological outlook, and risk behaviors among urban African American youth.

Abstract: Objectives Researchers have found a link between neighborhood risk factors and youth risk behaviors. However, the pathways by which this occurs remain poorly understood. This study sought to test a hypothesized pathway that suggests the influence of neighborhood risk on sexual risk and substance use among urban African American youth may operate indirectly via their psychological outlook about current and future opportunities. Methods Secondary data analysis using Structural Equation Modeling (SEM) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
0
15
1
Order By: Relevance
“…Depressive symptoms did not mediate associations between community violence victimization and alcohol, marijuana, or tobacco use among participants in the present sample. Although the results of one previous study demonstrated that a negative psychological outlook, a construct related to depression, mediated the link between neighborhood risk factors and substance use for African American youth (Wallace et al, 2017), the current study did not reveal a similar pattern. Depression may not reflect a mechanism through which community violence exposure is related to substance use in this population.…”
Section: Discussioncontrasting
confidence: 99%
“…Depressive symptoms did not mediate associations between community violence victimization and alcohol, marijuana, or tobacco use among participants in the present sample. Although the results of one previous study demonstrated that a negative psychological outlook, a construct related to depression, mediated the link between neighborhood risk factors and substance use for African American youth (Wallace et al, 2017), the current study did not reveal a similar pattern. Depression may not reflect a mechanism through which community violence exposure is related to substance use in this population.…”
Section: Discussioncontrasting
confidence: 99%
“…Individuals with a higher internalizing symptoms PRS were also more likely to be in the early-onset, decreasing class compared to the low steady subgroup when exposed to higher levels of community disadvantage. During early and middle adolescence, greater time spent in more socioeconomically deprived communities characterized by prevalent drug use may enable alcohol use among individuals with a higher polygenic load for internalizing symptoms given that they may be more likely to experience negative emotional states (Chassin et al, 2013; Hussong et al, 2011; Wallace et al, 2017; Wallace & Muroff, 2002). Indeed, lower community supervision of youth behavior, coupled with increased alcohol outlets in these neighborhoods, may facilitate early alcohol use among individuals with a higher internalizing symptoms PRS (Milam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These trajectories of alcohol use, however, reflect primarily European Americans that are socioeconomically diverse (e.g., Flory et al, 2004). Low-income, African American youth may experience different contextual stressors (e.g., higher levels of community disadvantage) that influence their alcohol use behaviors in a different manner than their European American, same-aged peers (Wallace & Muroff, 2002; Wallace, Neilands, & Phillips, 2017), warranting an examination of alcohol use behaviors in this population.…”
Section: Developmental Course Of Alcohol Use Across Adolescence and Young Adulthoodmentioning
confidence: 99%
“…In Freirian terms, this rising awareness represents a ''limit situation''-an awareness of the circumstances that limit a person or group, which may create a ''climate of hopelessness'' depending on whether they are perceived as ''fetter''-which may be cast off-or ''insurmountable barriers'' (Freire 1970(Freire /2000. As a sense of hopelessness in youths is associated with increased risks for poor behavioral health, including depression, sexual risk taking, and suicidality (Horwitz, Berona, Czyz, Yeguez, & King, 2017;Kagan et al, 2012;Wallace, Neilands, & Sanders Phillips, 2017), it is critical that program staff facilitate the photovoice process carefully. Rather than naturalizing and reifying relationships between participants and their circumstances, the photovoice analytic process must be directed toward emancipatory goals that enable participants to objectively perceive their environment and themselves in historical context, and thus subject to transformation.…”
Section: Discussionmentioning
confidence: 99%